Influencia del juicio de la gerencia en la determinación de la moneda funcional conforme a la Norma Internacional de Contabilidad N° 21, en las empresas agroexportadoras de la región La Libertad - Quezada Quevedo, Roberth Arturo (2016)
The globalized world in which we live requires us to adopt international financial reporting standards as the basis for the preparation and presentation of our financial statements in order to ensure the transparency and comparability of our financial information. The application of International Financial Reporting Standards entails the application of International Accounting Standard No. 21 Effects of changes in exchange rates of foreign currency for companies engaged in transactions in foreign currency, And especially for companies that carry out foreign trade such as agroexportadoras. Agribusiness companies, according to Promperú data, have exports with diversified destinations, as well as perform various commercial and non-commercial operations with both foreign customers and suppliers, which make the analysis complex to determine a functional currency for some of the companies in this sector. It is in these cases, in accordance with the provisions of IAS 21, that management plays an important role in determining the functional currency of the entity. The present investigation will use an exploratory and descriptive methodology with the objective of determining the influence of the judgment of the management in the determination of the functional currency in an agroexportadora company. Finally, it was possible to demonstrate that management's judgment is the factor that has the greatest influence on the determination of the functional currency, since that management body has sufficient knowledge about the development of the entity, and it is expected that its decision , Faithfully represent the economic effects of the company's transactions.